PENGARUH PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN PADA PERUSAHAAN TOP NINE TRAVEL DI KOTA GARUT - Devianti Nurazizah; Ramayani Yusuf; Rohimat Nurhasan (JURNAL EKONOMI PERJUANGAN, 2023)
This study aims to determine the effect of price perceptions on customer satisfaction at the Top Nine Travel Companies in Garut City. The method used in this research is a quantitative approach. The number of samples obtained was 50. The data analysis tool used was IBM SPSS version 26 software. To find out if the data was valid, reliable, and normally distributed, validity tests, reliability tests, and normality tests were used. To find out how close the relationship is and how much influence price perception has on customer satisfaction, a simple correlation test and a simple linear regression test are used. And to find out how far the model's ability to explain the variation of the dependent variable goes, the coefficient of determination test is used. From the test results, it is known that the data used is valid, reliable, and normally distributed. Also, price perceptions have a positive effect on customer satisfaction by creating a close relationship between the two and being able to explain variations in the dependent variable.